Modification of the principles of the ventral wall alloplasty - S. V. Vasiliev; T. A. Moshkova (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
The experience in modification of the surgical methods in implantation and fixation of the prostheses was estimated in 152 patients. Application of the author's methods significantly reduces postoperative complications and prevents hernia relapses.